A Breeding Estimated Particle Filter Research - Xiong Fang (Institute of Advanced Engineering and Science, 2015)
As the normal particle filter has an expensive computation and degeneracy problem, a propagation-prediction particle filter is proposed. In this scheme, particles after transfer are propagated under the distribution of state noise, and then the produced filial particles are used to predict the corresponding parent particle referring to measurement, in which step the newest measure information is added into estimation. Therefore predicted particle would be closer to the true state, which improves the precision of particle filter. Experiment results have proved the efficiency of the algorithm and the great predominance in little particles case. DOI: http://dx.doi.org/10.11591/telkomnika.v13i1.6712